Comparison of the maximum applicable stretch force after femtosecond laser-assisted and manual anterior capsulotomy - Auffarth, Gerd U.; Reddy, Kasu Prasad; Ritter, Roland; Holzer, Mike P.; Rabsilber, Tanja Marina (Journal of cataract and refractive surgery, 2013)
Purpose: To objectively measure the strength of the capsulotomy performed with a femtosecond laser-assisted technique or performed manually in a pig-eye laboratory study. - Setting - International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - Design - Experimental study. - Methods - Ten fresh pig eyes were randomly assigned to femtosecond laser-assisted capsulotomy or manual capsulotomy. The capsule was immersed in hyaluronic acid, and retractors were fixed in the capsule opening with a pull-force measuring device. The force necessary to break the capsulotomy was measured in millinewtons (mN); the maximum stretching ratio was also assessed. - Results - The observed mean rupture force (ie, maximum amount of force measured immediately before tissue rupture) was 113 mN ± 12 (SD) in the laser-assisted procedure and 73 ± 22 mN in the manual procedure (P<.05). The stretching ratios were 1.60 ± 0.10 (femtosecond) and 1.35 ± 0.04 (manual) (P<.05). - Conclusion - In this laboratory pig-eye study, femtosecond laser-assisted capsulotomy resulted in a significantly stronger anterior capsule opening than the standard manually performed capsulotomy. - Financial Disclosure - Drs. Auffarth, Reddy, and Holzer have received research and travel grants from Technolas Perfect Vision GmbH. Mr. Ritter is an employee of Technolas Perfect Vision GmbH, Munich, Germany.
Gesehen am 22.10.2020
First published: 12 December 2012